Homomorphism between Rings - S., Vinod; G. S., Biju; N. S., Minikumari (Communications in Mathematics and Applications, 2020)
In this paper, using elementary algebra and analysis, we characterize and compute all ring homomorphism from \(\mathbb{Z}^n\) to \(\mathbb{Z}^m\) and from \(\mathbb{Q}^n\) to \(\mathbb{Q}^m\). Also, we characterize and compute all continuous ring homomorphism from \(\mathbb{R}^n\) to \(\mathbb{R}\).